Food Franchising Entrepreneurship in Singapore - Kow, WaiYee@ZoeyKoh (2009)
Purpose – This report aims to bridge the concepts of entrepreneurship, strategic management and franchising model to develop a framework for the food business in Singapore. Methodology – Based on entrepreneurship literature search, the paper identifies the importance of whole brain entrepreneurial team approach in the food business due to its nature of broad consumers’ base; entrepreneurial behaviour in information source to identify opportunities and innovation in food product, process and market. Strategic management literature for screening the environment and opportunities identification like PESTEL and consumer behaviours models will be assessed. The pros and cons of the franchising model will also be explored. The interviews on the small group of entrepreneurs were carried out to understand their view of business outlook, entrepreneurship characteristics and their opinion on the franchising model. Analysis – This report provides an analysis of the Singapore food macro environment as a tool to identify food business opportunities and threats. The open kitchen business concept, innovation in product assortment, marketing strategies and whole brain analysis on the brand name of BreadTalk are successfully analyzed and defined as these are their success factors. Further analysis on innovation in product, process and market was carried out and compared among three success case studies on BreadTalk, Old Chang Kee and McDonalds to understand their innovative indicators. Porter 5 forces method is used to review the competitiveness of the food business. The disadvantages of the franchising model applied to food industry has minor impacts with the prerequisite of success business model are established. Results – The results suggest the importance of understanding the link between entrepreneurship, strategy and franchising as a whole is essential in the food business opportunities identification process; understanding your customers, knowing your strengths and weaknesses to form the entrepreneurial team, being alert to environmental changes, innovative service or product are the keys to success in the Singapore food business.